Pharmacological potential of parasitic Angiosperms against microorganisms (2023)
Parasitic habit plants arouse great interest for their extraordinary growth adaptations and produce different secondary metabolites that allow them to survive the extreme conditions in which they develop. This can provide a range of compounds with multiple uses. However, those plants have been poorly explored and there is very little information about their natural compounds, some healing properties attributed to several communities have been scientifically supported. Articles were consulted in databases (Google Scholar, PubMed, Scielo, Science Direct, Scopus) considering the biological activity reported until June 2021. Parasitic plants present mainly antibacterial activity, some species antifungal moderate activity, and to a lesser extent were found reports of antiprotozoal activity. The composition of parasitic plants should continue to be investigated, which could be an alternative to combat various microorganisms that cause diseases, even resistant to traditional medicines.